2006
DOI: 10.1111/j.1365-2907.2006.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of wildlife rabies in Europe

Abstract: 1. The number of wildlife rabies cases has increased in Europe in recent years. We review the epizootiology of wildlife rabies in Europe, paying special attention to recent changes to the situation of two important vector species: the red fox and the raccoon dog. Red fox Vulpes vulpes has been the main vector of rabies since 1945, but the number and proportion of raccoon dog Nyctereutes procyonoides cases has rapidly increased during the past few years, particularly in north-eastern Europe. 2. The transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 78 publications
(114 reference statements)
2
62
0
3
Order By: Relevance
“…The fox density in one area of Svalbard, in Adventdalen and Sassendalen (900 km 2 ), has been estimated to 0.1-0.15 animals per km 2 (Eide, 2002), considerably lower than in other arctic regions with arctic foxes of the inland ecotype. In Sweden, the density of red foxes (Vulpes vulpes) is estimated to be 0.2-0.4 foxes per km 2 , which is regarded as too low for the generation of rabies epizootics (Holmala and Kauhala, 2006). Thus, the even-lower and more-stable fox population density in Svalbard can explain the lack of reported epizootics.…”
Section: Sample Identification Sequencementioning
confidence: 99%
“…The fox density in one area of Svalbard, in Adventdalen and Sassendalen (900 km 2 ), has been estimated to 0.1-0.15 animals per km 2 (Eide, 2002), considerably lower than in other arctic regions with arctic foxes of the inland ecotype. In Sweden, the density of red foxes (Vulpes vulpes) is estimated to be 0.2-0.4 foxes per km 2 , which is regarded as too low for the generation of rabies epizootics (Holmala and Kauhala, 2006). Thus, the even-lower and more-stable fox population density in Svalbard can explain the lack of reported epizootics.…”
Section: Sample Identification Sequencementioning
confidence: 99%
“…Both canids can host many species of parasites infecting foxes. The raccoon dog is a vector of rabies (Holmala & Kauhala 2006) and parasites particularly of Echinococcus multilocularis, as showed by some infected raccoon dogs found in Germany, of Sarcoptes scabiei (Shibata & Kawamichi 1999;Ninomiya & Ogata 2005), and of Trichinella spp. (Oksanen et al, 1998;Oivanen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Botvinkin et al (1985) demonstrated in the laboratory that small rodents would not fall ill during hibernation, but would show rabies signs shortly after becoming active again. A similar effect is expected for rabies incubation in hibernating raccoon dogs (Cerkasskij, 1980;Holmala and Kauhala, 2006).…”
Section: Introductionmentioning
confidence: 73%